Weaving Intersectional Rhetoric: The Digital Counternarratives of Indigenous Feminist Bloggers (ENTHYMEMA, 2017)
Indigenous feminist bloggers weave an intersectional, rhetorical story that lances the core of American popular culture and misinformed imaginations. The Native American women bloggers introduced in this essay are unknown to most non-Native Americans, most rhetoric scholars, and most feminists, but should be on our radar because of their refusal to be constrained by colonialist binaries, single rhetorical forms, or imposed boundedness to the margins. These Indigenous feminists practice in the digital space to reinforce and reclaim rhetorical sovereignty as an outcome for themselves and their communities. Once the weaving is complete, the resultant warmth of rhetorical sovereignty provides some protection from the cold colonial stories of erasure and absence.